INNOVATION MALANG BLACK APPLE - Morell, Gerry; Tanius, Billy; Surjawan, Iwan; Ni Ketut Veri Kusumaningrum (INSPIRE : Journal of Culinary, Hospitality, Digital & Creative Arts and Event, 2024)
The study focuses on developing innovation in processing Malang Apples through advanced fermentation techniques to create "Black Malang Apple," a novel agricultural product. Utilizing a Research and Development (R&D) approach, the research explores systematic exploration and development of fermented fruit products. The primary motivation stems from the need to enhance the nutritional value of local fruits and create innovative value-added processing methods for agricultural commodities. The fermentation process transforms traditional Malang Apples through a specialized blackening technique, resulting in significant changes to the fruit's characteristics. Comparative analysis revealed that the fermented product demonstrates substantially improved nutritional profiles compared to fresh Malang Apples. The research examined critical aspects such as nutritional content, sensory properties, and potential health benefits. Experimental results highlighted remarkable transformations in the apple's physical and chemical properties. The fermentation method produced notable modifications in shape, taste, and texture, creating a unique food product with enhanced nutritional characteristics. This innovative approach represents a promising avenue for local fruit processing and agricultural product development.